Secrecy outage probability of DF‐based C‐NOMA under half and full duplex - Shilpi Gadi; S. Pratap Singh; Amit Kumar; Rajneesh Kumar Singh; Ghanshyam Singh (IET Communications, 2023)
Abstract Cooperative Non‐orthogonal Multiple Access (C‐NOMA) is projected as the dominant technology for 5G and beyond. Also, physical layer security, due to the presence of eaves‐dropper, is a bottleneck security concern for any open link wireless system. This manuscript presents a novel Decode & Forward (DF)‐based C‐NOMA system in the presence of two eavesdroppers. Moreover, both half duplex and full duplex schemes are included in the analysis. Thereby, separate expressions for Secrecy Outage Probability (SOP), being among the most crucial performance measures in physical layer security, are produced and examined for the system under consideration. Specifically, first of all, novel expression of SOP for C‐NOMA systems under both Half Duplex (HD) and Full Duplex (FD) schemes is derived for the case when only eavesdropper one (E1) attacks on link source to device one (S‐D1). Thereafter, expressions of SOP for the C‐NOMA system under both HD and FD schemes are derived, considering presence of E1 and E2 on the links, source to device one (S‐D1) and source to device two (S‐D2), respectively. Further, for both the duplexes, the effect of eavesdropper one (E1) and eavesdropper two (E2) on the links, S‐D1 and S‐D2, respectively, is analyzed. The presented analysis is useful in the technological development level of C‐NOMA in the presence of multiple eavesdroppers. The simulated results show perfect agreement with the theory.